فعالية تطبيق لعبة سلسلة الهمس لترقية مهارة الاستماع لدى طلاب الصف الثاني من المدرسة الدينية بمعهد سونان غيري الإسلامية سورابايا - Faruq Abdul Muid (PALAPA, 2023)
The objectives of the research that the researchers conducted were to find out how the ability of Maharah Istima' was for Class II students at Madrasah Diniyah Pondok Pesantren Sunan Giri Surabaya, to find out how Maharah Istima' was able to play through the Whispering Chain Game Method for Class II students at Madrasah Diniyah Pondok Pesantren Sunan Giri. Surabaya, and to find out the effectiveness of the application of the Whisper Chain Game Method to Increase the Maharah Istima' of Class II Madrasah Diniyah Students, Pondok Pesantren Sunan Giri Surabaya. The type of this research is Quantitative Research using Pre Experimental Design method. The subject of this research is the second grade students of Madrasah Diniyah Pondok Pesantren Sunan Giri Surabaya. Meanwhile, the object of research is the Whispering Chain Game Method to Increase Maharah Istima' for Class II Students of Madrasah Diniyah Pondok Pesantren Sunan Giri Surabaya, then the data collection techniques that the author chooses are interviews, observations, and tests. The results of the study before the application of the whisper chain game method was that 50% of students had scores in the low and very low categories, after the application of the whisper chain game method and the Post Test, 88% of students had high grades, so it can be concluded that the whisper chain game method is effective in increasing the maharah istima’ for Class II students of Madrasah Diniyah Pondok Pesantren Sunan Giri Surabaya.